OVERVIEW OF "DISCOVER THE POTENTIAL" CAMPAIGN ON DIGITAL MEDIA AS A TURKEY'S NATION BRANDING STRATEGY - Raesita Rakhmawati Rosadi (PRoMEDIA, 2022)
Nation Branding is a way for countries to create differentiation and uniqueness from other countries through branding. A Public Relations campaign can communicate a nation's brands that will attract business, tourism, and investment. Turkey is one of many countries that have started a nation branding campaign called 'Turkey: Discover the Potential' in 2014. Head of Turkey Exporters Assembly (TIM) Mehmet Büyükekşi stated that Discover the Potential is an offer to the whole world to come and discover the potential in the country. This study will analyze 'Turkey: Discover the Potential Campaign' communicated through digital media; website, Facebook, Instagram, Twitter, and LinkedIn. This study then describes the digital media channels that have been used and optimization efforts that the 'Turkey can carry out: Discover the Potential Campaign' team in terms of content and technical use of the campaign media. 'Turkey: Discover the Potential Campaign' has seen this opportunity to spread the messages to the whole world through digital media. It uses every digital media platform available, including website, Facebook, Instagram, Twitter, and LinkedIn. An important thing that is missed from this campaign is that each social media platform has its characteristics and specialization. As for Turkey, this campaign can be a tool to communicate and promote national products, increase the number of exported products, and invite potential investors to invest and do business in the country.